2016
DOI: 10.1212/nxg.0000000000000096
|View full text |Cite
|
Sign up to set email alerts
|

KCNQ2 encephalopathy

Abstract: Objective:To advance the understanding of KCNQ2 encephalopathy genotype–phenotype relationships and to begin to assess the potential of selective KCNQ channel openers as targeted treatments.Methods:We retrospectively studied 23 patients with KCNQ2 encephalopathy, including 11 treated with ezogabine (EZO). We analyzed the genotype–phenotype relationships in these and 70 previously described patients.Results:The mean seizure onset age was 1.8 ± 1.6 (SD) days. Of the 20 EEGs obtained within a week of birth, 11 sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
113
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(119 citation statements)
references
References 36 publications
5
113
1
Order By: Relevance
“…Genetic research has produced advances that have transformed our knowledge of the pathogenesis underlying and potential targeted treatments for epilepsy . The SCN1A, SCN2A, and KCNQ2 genes have all emerged as prominent epilepsy genes and have been associated with a broad array of seizure phenotypes ranging from benign to epileptic encephalopathy . Seizures were refractory in patients with a serious phenotype.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Genetic research has produced advances that have transformed our knowledge of the pathogenesis underlying and potential targeted treatments for epilepsy . The SCN1A, SCN2A, and KCNQ2 genes have all emerged as prominent epilepsy genes and have been associated with a broad array of seizure phenotypes ranging from benign to epileptic encephalopathy . Seizures were refractory in patients with a serious phenotype.…”
Section: Discussionsupporting
confidence: 89%
“…According to a network analysis of the consequences of loss‐of‐function in most SCN1A mutations, we avoided the use of SCBs in these patients. However, the use of selected SCBs, such as phenytoin and LCM, produced significant improvements in some of the patients harboring SCN2A or KCNQ2 variants in our group, similar to the findings of previously reported studies . Meanwhile, a new and selective drug that acts as a ligand for high‐affinity synaptic vesicle protein 2A, brivaracetam, had little effect in patients with the STXBP1 variant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noteworthy, at variance with Kv7.2 R325G channels, homomeric Kv7.2 R325A channels, similarly to Kv7.1 channels carrying the equivalent R360A mutation both in the absence44 or in the presence45 of KCNE1 subunits, were functional, although they displayed a reduced current amplitude4346; the α-helix-stabilizing propensity of alanine relative to glycine47 provides a plausible explanation for such relevant functional difference. Noteworthy, all Kv7.2 missense variants causing EE (including the c.973A > G leading to the R325G mutation herein investigated) are de novo substitutions of a single nucleotide748. Instead, a substitution of at least two nucleotides would be needed to generate the arginine-to-alanine mutation studied by Telezhkin43; thus, the R325A mutation is less likely to occur in vivo .…”
Section: Discussionmentioning
confidence: 92%
“…Additional in vitro and mouse in vivo studies found that treatment with retigabine ameliorates the effects of these dominant-negative mutations and can attenuate seizure activity in mouse models 132,133 . A small retrospective study of 11 children with KCNQ2 -related epileptic encephalopathy treated with retigabine found that 3 of 4 patients treated before 6 months of age had seizure improvement, whereas clinical response was less impressive for patients treated after 6 months, with only 2 out of 7 showing improvement 134 .…”
Section: Precision Medicine and Drug Developmentmentioning
confidence: 99%